2012
DOI: 10.1177/1071181312561481
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the Technology Acceptance Model with Trust: Commercial Drivers’ Attitudes towards Monitoring and Feedback

Abstract: This study evaluates truck drivers' attitudes toward an on-board monitoring system (OBMS), using an extended version of the Technology Acceptance Model (TAM) that accounts for drivers' trust in OBMS. Crashes that involve trucks incur a high cost to society and driver-related factors contribute to about one third of all large truck fatal crashes in the US. Therefore, safety initiatives that can increase drivers' awareness of their risky behaviors are highly desirable. In-vehicle feedback systems are designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…We measured acceptance focusing on both user's perceptions and intention to use the system. Thus, we used the scale from Van der Laan et al (1997), as well as measured the constructs included in the CTAM with the scales from Osswald et al (2012) and Ghazizadeh, Peng, Lee, and Boyle (2012). The Van der Laan et al (1997) scale includes nine semantic differential items representing different attitudes toward the system.…”
Section: Acceptancementioning
confidence: 99%
“…We measured acceptance focusing on both user's perceptions and intention to use the system. Thus, we used the scale from Van der Laan et al (1997), as well as measured the constructs included in the CTAM with the scales from Osswald et al (2012) and Ghazizadeh, Peng, Lee, and Boyle (2012). The Van der Laan et al (1997) scale includes nine semantic differential items representing different attitudes toward the system.…”
Section: Acceptancementioning
confidence: 99%
“…Scientists suggest a strong relationship between information quality, system quality, service quality, and technology acceptance model. Furthermore, this study has extended the technology acceptance model with trust, because trust is an essential factor in the relationship of three qualities and technology acceptance model (Ghazizadeh et al, 2012;Yang et al, 2015), taking in to account recent studies in consumer behaviour (Ahmed, Vveinhardt, & Streimikiene, 2017;Cachero-Martinez & Vazquez-Casielles, 2017;Debkowska, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…All processes changed from traditional to computerized systems, which is a more convenient and efficient method to save financial resources and time. This phenomenon is widely analysed by scientists (Disney et al, 2018;Ghazizadeh et al, 2012;Martens et al, 2017;Roy et al, 2018;Skackauskiene et al, 2016;Yang et al, 2015), but attention to the developing countries and their acceptance of ICT innovation is missing, as well as a lack of integrity of aspects, such as consumer behaviour and technology acceptance (electronic ticketing in particular). Therefore, country and model level alternatives should be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in transportation area also adopted TAM to find the essential factors influencing intention to use particular system such as driving assistance system (e.g. [24][25] [26]), traffic information system [27], mobile travel guide system [28], etc. However, studies in the specific area of ATIS such traffic information applications are still insufficient.…”
Section: B Theoretical Background and Hypotheses Frameworkmentioning
confidence: 99%
“…Meanwhile, Ghazizadesh et al [24] also found the importance of trust in transportation area. They discovered a significant effect of trust on behavioral intention to use driving assistance system.…”
Section: Trust In Application (Tia)mentioning
confidence: 99%